Analisis Pertumbuhan Asset, Earning Volatility, Dan Debt To Equity Rasio Terhadap Volatilitas Harga Saham Pada Sub Sektor Otomotif Dan Komponen - Alief Sofyan Lanang; Alwi Alwi; Hanifah Muthiah (EBISMA : Jurnal Ekonomi, Bisnis, Manajemen dan Akuntansi, 2025)
This study aims to analyze the effect of asset growth, earning volatility, and debt to equity ratio (DER) on stock price volatility in automotive and component sub-sector companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. The method used is an associative quantitative approach using secondary data from five selected companies through purposive sampling techniques based on data availability and consistency of financial reporting. Data analysis was carried out using classical assumption tests and multiple linear regression. The results show that partially, asset growth and earning volatility do not have a significant effect on stock price volatility, while DER has a significant positive effect. Simultaneously, these three variables have a significant effect on stock price volatility. These findings imply that a company's funding structure, particularly debt levels, plays an important role in stock price fluctuations and needs to be an investor concern in investment decision-making.